Retreatment with brentuximab vedotin in patients with CD30-positive hematologic malignancies - Bartlett, Nancy L; Chen, Robert; Fanale, Michelle A; Brice, Pauline; Gopal, Ajay; Smith, Scott E; Advani, Ranjana; Matous, Jeffrey V; Ramchandren, Radhakrishnan; Rosenblatt, Joseph D; Huebner, Dirk; Levine, Pamela; et al. (Journal of hematology and oncology, 2014)
Background Brentuximab vedotin is a CD30-directed antibody-drug conjugate. Retreatment with brentuximab vedotin monotherapy was investigated in patients with CD30-positive Hodgkin lymphoma (HL) or systemic anaplastic large cell lymphoma (ALCL) who relapsed after achieving complete or partial remission (CR or PR) with initial brentuximab vedotin therapy in a previous study (ClinicalTrials.gov NCT00947856). Methods Twenty-one patients with HL and 8 patients with systemic ALCL were retreated; 3 patients with systemic ALCL were retreated twice. Patients generally received brentuximab vedotin 1.8 mg/kg intravenously approximately every 3 weeks over 30 minutes as an outpatient infusion. The primary objectives of this study were to assess safety and to estimate antitumor activity of brentuximab vedotin retreatment. Results The objective response rate was 60% (30% CR) in HL patients and 88% (63% CR) in systemic ALCL patients. The estimated median duration of response for patients with an objective response was 9.5 months (range, 0.0+ to 28.0+ months) at the time of study closure. Of the 19 patients with objective response, 7 patients had not had an event of disease progression or death at the time of study closure; duration of response for these patients ranged from 3.5 to 28 months. Of the 11 patients with CR, 45% had response durations of over 1 year. Adverse events (AEs) occurring in ≥25% of patients during the retreatment period were generally similar in type and frequency to those observed in the pivotal trials of brentuximab vedotin monotherapy, with the exception of peripheral neuropathy, which is known to have a cumulative effect. Grade 3 or higher events were observed in 48% of patients; these were generally transient and managed by dose modifications or delays. Deaths due to AEs occurred in 3 HL patients; none were considered to be related to brentuximab vedotin retreatment. Discussion With the exception of a higher rate of peripheral motor neuropathy, retreatment with brentuximab vedotin was associated with similar side effects seen in the pivotal trials. Conclusions Retreatment with brentuximab vedotin monotherapy is associated with response rates in 68% (39% CR) of patients with relapsed HL and systemic ALCL. Trial registration United States registry and results database ClinicalTrials.gov NCT00947856 .